Construction of a ceRNA-based lncRNA–mRNA network to identify functional lncRNAs in premature ovarian insufficiency - Luo, Chao; Zhang, Jiakai; Bo, Le; Wei, Lun; Yang, Guangzhao; Gao, Shasha; Mao, Caiping (Frontiers in Genetics, 2022)
Premature ovarian insufficiency, characterized by ovarian infertility and low fertility, has become a significant problem in developed countries due to its propensity for late delivery. It has been described that the vital role of lncRNA in the development and progression of POI. However, lncRNA expression profiles and their role in initiation and progression of Premature ovarian insufficiency remain largely unclear at present. The aim of this work was to create a POI-based lncRNA-mRNA network (POILMN) to recognize key lncRNAs. The microarray data can be downloaded from the Gene Expression Omnibus(GEO) database, accession number GSE135697. Differently expressed mRNAs(DEGs) and differently expressed lncRNAs(DELs) were achieved by using the Annoprobe and Limma R packages. RNA–RNA pairs (including lncRNA–miRNA pairs and miRNA–mRNA pairs) were obtained from Starbase and miRTarBase databases, respectively. The lncRNA-mRNA network (POILMN) construction through tinyarray R package and hypergeometric distribution. To identify key lncRNAs, we used CentiScaPe plug-in Cytoscape as a screening tool. Functional enrichment (GO annotation, KEGG) were performed by the R clusterProfiler package. Then we predicted the subcellular localization of key lncRNAs via Lnclocator tools. In total, 244 different expressed lncRNAs(DELs) and 288 different expressed mRNAs(DEGs) were obtained in this study. And 177 lncRNA/mRNA pairs (including 39 lncRNAs and 86 mRNAs) were selected by the hypergeometric test with P < 0.01 and counts > 3. Furthermore, we identified four lncRNAs (HCP5, NUTM2A-AS1, GABPB1-IT1, SMIM25) intersection by topological analysis between two centralities (Degree and Betweenness). Then we explored their subnetwork GO and KEGG pathway enrichment analysis and predicted key lncRNAs locations. Here we have provided strong evidence for a relationship with apoptosis, DNA repair damage, and energy metabolism terms and pathways in the key lncRNAs in our POILMN. However, more experiments are needed to confirm the functional significance of such predicted lncRNA/mRNA. Our study identified four long non-coding RNA molecules that may have relevance to the progress of premature ovarian insufficiency. What's more, molecular pathways involved in apoptosis, DNA repair damage, and energy metabolism may be closely associated with disease progression and worsening of symptoms.